Corrosion of phosphor bronze in different biodiesel blends / Rathinee Balakumar - Rathinee, Balakumar (2015)
Biodiesel fuel is gaining rapid recognition around the globe as a reliable alternative to the use of petroleum fuel in the automotive industry. This safer, greener, renewable energy source originates from naturally forming feedstocks such as animal fats and vegetable oils. Biodiesel blends consist of mixtures of biodiesel with diesel at different composition. Biodiesel fuel is much more corrosive when compared to petroleum fuel, thus giving rise to many compatibility issues with the material construction of a typical combustion ignition engine. This research studies the effects of Tert-butylamine and Benzotriazole additive on the corrosion behaviour of phosphor bronze in different diesel/biodiesel blends. The biodiesel feedstock used in the research originates from palm oil. The corrosion behaviour of phosphor bronze was studied through immersion test in B0, B20 (20% biodiesel and 80% diesel), B50 (50% biodiesel and 50% diesel) and B100 for 1440 hours. Similar test was carried out with the addition of additive Tert-butylamine and Benzotriazole in B20 and B100. The test coupons were weighed before and after the immersion test to determine the weight loss measurement and calculate the corrosion rate. The metal surface was characterized by Scanning Electron Microscopy and Energy Dispersive X-Ray, while fuels was analysed by measuring Total Acid Number and density. The test result indicates that biodiesel is more corrosive to phosphor bronze sample when compared to diesel. Increasing biodiesel volume in the immersion solution increases the corrosion attack on phosphor bronze. The presence of additive Tert-butylamine and Benzotriazole, retards the corrosion attack and protects the phosphor bronze from further deteriorating. Benzotriazole was found to be a more efficient and effective corrosion inhibitor for phosphor bronze in biodiesel environment.